Major curricula as structures for disciplinary acculturation that contribute to student minoritization - Fiorini, Stefano; Tarchinski, Nita; Pearson, Meaghan; Valdivia Medinaceli, Montserrat; Matz, Rebecca L.; Lucien, Juniar; Lee, Hye Rin; Koester, Benjamin; Denaro, Kameryn; Caporale, Natalia; Byrd, W. Carson (Frontiers in Education, 2023)
Institutions of higher learning are characterized by multiple, often intersecting, social-educational structures aimed at regulating the conditions by which a degree is ultimately granted. The sequence of courses that students must take for a degree is one such structure. Building on the Sloan Equity and Inclusion in STEM Introductory Courses (SEISMIC) Collaboration's prior work, we provide a comparative view of students' pathways through selected curricula at two participating institutions. We apply process analytics to students' course enrollments as a tool to reveal features of the curricula and the associated impacts on students' progressions to degree. Given the high enrollment in biologyrelated degree programs at these institutions, we focus on those and ask two questions: 1) Is the intended progression through the curriculum the one most commonly experienced by the students? and 2) does the maintenance of coherence and socialization into the discipline act in a similar way on individuals of different socio, economic and demographic backgrounds? Curriculum analytics tends to be driven by a reductionist view of its structure. Instead, we view the curriculum as a tool for disciplinary acculturation, revealing aspects of students' transitions through educational systems not captured by commonly applied course or retention analyses. Curricular structures and the constraints they impose impact the way individual students become members of a scholarly community by acting as a cultural and social homogenizing agent. Across the curricula and institutions in this study,